Impact of duration of antibiotic therapy in central venous catheter-related bloodstream infection due to Gram-negative bacilli. (26th June 2020) - Ruiz-Ruigómez, María; Fernández-Ruiz, Mario; San-Juan, Rafael; López-Medrano, Francisco; Orellana, María Ángeles; Corbella, Laura; Rodríguez-Goncer, Isabel; Hernández Jiménez, Pilar; Aguado, José María
Abstract: Background: A progressive increase in the incidence of catheter-related bloodstream infection (CRBSI) due to Gram-negative bacilli (GNB) has been reported. Current guidelines recommend antibiotic treatment for at least 7–14 days, although the supporting evidence is limited. Methods: We performed a retrospective single-centre study including all patients with a definite diagnosis of GNB CRBSI from January 2012 to October 2018 in which the central venous catheter (CVC) was removed. The occurrence of therapeutic failure [clinical failure (persistence of symptoms and laboratory signs of infection), microbiological failure (persistent bacteraemia or relapse) and/or all-cause 30 day mortality] was compared between episodes receiving short [≤7 days (SC)] or long courses [>7 days (LC)] of appropriate antibiotic therapy following CVC removal. Results: We included 54 GNB CRBSI episodes with an overall rate of therapeutic failure of 27.8% (15/54). Episodes receiving SC therapy were more frequently due to MDR GNB [60.9% (14/23) versus 34.5% (10/29); P  = 0.058] and had higher Pitt scores [median (IQR) 1 (0–4) versus 0 (0–2); P  = 0.086]. There were no significant differences in the rate of therapeutic failure between episodes treated with SC or LC therapy [30.4% (7/23) versus 27.6% (8/29); OR 1.15; 95% CI 0.34–3.83; P  = 0.822]. The use of SCs was not associated with increased odds of therapeutic failure in any of the exploratory models performed. Conclusions: The administration of appropriate antibiotic therapy for ≤7 days may be as safe and effective as longer courses in episodes of GNB CRBSI once the CVC has been removed.